Analisis Model Interaksi antara Tenaga Medis dan Keluarga Pasien Hemodialisis dalam Mendukung Proses Pengobatan di Unit Hemodialisa RS UNHAS Makassar - Andi Aghnie Aulya Asnur; Heris Hendriana; Yen Efawati (ManBiz: Journal of Management and Business, 2025)
Chronic Kidney Disease (CKD) is a major global health problem that requires long-term therapy such as hemodialysis. The success of hemodialysis treatment is strongly influenced by the quality of interaction between healthcare providers and patients’ families, particularly in providing emotional support, information, and accompaniment throughout the treatment process. This study aims to analyze the interaction model between medical personnel and families of hemodialysis patients and to explore the factors that influence communication effectiveness in supporting treatment adherence and improving patients’ quality of life. This research employed a qualitative phenomenological approach to explore the lived experiences of healthcare professionals and family members in the Hemodialysis Unit of Hasanuddin University Hospital, Makassar. Data were collected through in-depth interviews, participatory observation, and documentation review. A total of 20 participants took part in the study, consisting of 10 healthcare workers and 10 family caregivers. Data were analyzed using thematic analysis involving coding, categorization, and interpretation of phenomenological meanings. The findings indicate that therapeutic communication, empathy, and openness form the foundation of effective interactions between healthcare providers and families. Families play an essential role in offering emotional support, ensuring adherence to dialysis schedules, participating in medical decision-making, and providing logistical assistance. The study also identifies several barriers to effective interaction, including emotional distress, limited knowledge, time constraints, and differences in educational background. This research proposes an interaction model that emphasizes two-way collaboration, continuous education, and family-centered communication. This study contributes to strengthening therapeutic communication practices in hemodialysis settings and provides a foundation for developing policies that enhance humanistic and collaborative care between medical personnel, patients, and their families.